Pemanfaatan Gulma Air sebagai Pupuk Organik Padat untuk Peningkatan Produksi Bawang Merah: Ultilization of Water Weeds as Solid Organic Fertilizer for Increased Shallot Production - Masjidi, Muna Aida; Norahman, Sahid; Yulianti, Hairini; Istiqomah, Nurul (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Most farmers typically plant rice only once a year, leading to weed-infested fields. Using aquatic weeds as Pupuk Organik Padat (POP) is seen as a viable approach to weed control. This study aims to explore the interaction and effects of different types and doses of aquatic weeds as POP and identify the most effective combination. The research was conducted in Banua Budi Village, Barabai District, Hulu Sungai Tengah Regency, from June to October 2023, utilizing a Randomized Complete Block Design (RAK) with 2 factors, grouped based on tuber diameter. The types of POP (J) include three levels: j1: POP water mimosa, j2: POP lotus, j3: POP banto grass. The POP dosage factor consists of two levels: d1: 20 ton.ha-1 equivalent to 2 kg/plot, d2: 30 ton.ha-1 equivalent to 3 kg/plot. There were six combinations with four replications, resulting in 24 experimental units. Each experimental unit comprised 16 plants, and four sample plants were observed, making a total of 96 sample plants. The findings indicate that the interaction and individual treatment types had no significant impact on the observed variables. However, when considering the single treatment of water weed with POP dosage, there was a notable effect. The optimal dosage was found to be d2: 30 ton.ha-1 or equivalent to 3 kg/plot. Keywords : Sallots, Solid organic fertilizer, Production